3/5 nhân x -1/2 =a
b, ( x - 3/4 ) + 1/2 = 5va 3/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
X x \(\dfrac{3}{4}\)+ X x\(\dfrac{1}{5}\)+ X x \(\dfrac{1}{20}\)+ X= 1000
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 1:
a. $3\frac{2}{3}+2\frac{1}{2}=(3+2)+(\frac{2}{3}+\frac{1}{2})=5+\frac{7}{6}=6+\frac{1}{6}=6\frac{1}{6}$
b. \(2\frac{1}{2}\times 3\frac{2}{5}=\frac{5}{2}\times \frac{17}{5}=\frac{17}{2}\)
c.
\(3\frac{1}{3}: 4\frac{1}{4}=\frac{10}{3}: \frac{17}{4}=\frac{40}{51}\)
d.
\(3\frac{1}{2}+4\frac{5}{7}-5\frac{5}{14}=(3+4-5)+(\frac{1}{2}+\frac{5}{7}-\frac{5}{14})=2+\frac{6}{7}=2\frac{6}{7}\)
Câu 2:
a. $x\times \frac{2}{7}=\frac{6}{11}$
$x=\frac{6}{11}: \frac{2}{7}=\frac{21}{11}$
b. $x: \frac{3}{2}=\frac{1}{4}$
$x=\frac{1}{4}\times \frac{3}{2}=\frac{3}{8}$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{1}{2}+\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+\frac{1}{30}+\frac{1}{42}\)
= \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+\frac{1}{5.6}+\frac{1}{6.7}\)
= \(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}\)
= \(1-\frac{1}{7}\)
= \(\frac{7}{7}-\frac{1}{7}\)
= \(\frac{6}{7}\)
2) \(\frac{7}{4}-x.\frac{4}{3}=\frac{5}{19}\)
\(x.\frac{4}{3}=\frac{7}{4}-\frac{5}{19}\)
\(x.\frac{4}{3}=\frac{133}{76}-\frac{20}{76}\)
\(x.\frac{4}{3}=\frac{113}{76}\)
\(x=\frac{113}{76}:\frac{4}{3}\)
\(x=\frac{399}{304}\)
VẬY \(x=\frac{399}{304}\)
b) \(\left(x+\frac{3}{4}\right).\frac{5}{7}=\frac{10}{9}\)
\(\left(x+\frac{3}{4}\right)=\frac{10}{9}:\frac{5}{7}\)
\(x+\frac{3}{4}=\frac{14}{9}\)
\(x=\frac{14}{9}-\frac{3}{4}\)
\(x=\frac{29}{36}\)
Vậy \(x=\frac{29}{36}\)
c) \(x.\frac{1}{2}+\frac{3}{2}.x=\frac{4}{5}\)
\(x.\left(\frac{1}{2}+\frac{3}{2}\right)=\frac{4}{5}\)
\(x.2=\frac{4}{5}\)
\(x=\frac{4}{5}:2\)
\(x=\frac{2}{5}\)
Vậy \(x=\frac{2}{5}\)
Chúc bạn học tốt !!!
![](https://rs.olm.vn/images/avt/0.png?1311)
1/
\(B=\frac{\left(3-1\right)\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)-3^{16}}{4}\)
\(=\frac{\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)-3^{16}}{4}\)
\(=\frac{\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)-3^{16}}{4}\)
\(=\frac{\left(3^8-1\right)\left(3^8+1\right)-3^{16}}{4}\)
\(=\frac{3^{16}-1-3^{16}}{4}=\frac{-1}{4}\)
2/
a, (x-5)2-(x+3)2=1
<=>(x-5+x+3)(x-5-x-3)=1
<=>-16.(x-1)=1
<=>x-1=-1/16
<=>x=15/16
b, (2x-1)2-(2x-3)2=4
<=>(2x-1+2x-3)(2x-1-2x+3)=4
<=>-8(x-1)=4
<=>x-1=-1/2
<=>x=1/2